Dinamika Social Integration dan Alkuturasi Budaya Medan di Bandung - Rahma Adelia, Mega; Saputra, Deni; Rambe, Ira Hasianna; Amini, Nadia Ushfuri (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
This research focuses on the process of social integration and cultural acculturation between the people of Medan and the Sundanese people in the city of Bandung. By applying a descriptive qualitative method using Alcutation Theory, the data collection process is carried out through direct observation to understand the dynamics of social interaction, semi-structured interviews to gain in-depth insights from participants, and literature studies that serve as the basis for strengthening the theory and context of research. This research aims to describe how the people of Medan adapt to Sundanese culture while maintaining their cultural identity. The acculturation process between Medan and Sundanese cultures also enriches the cultural diversity in the city of Bandung, creating a harmonious relationship in the midst of a multiethnic society.